IMPLEMENTATION OF STAD-TYPE COOPERATIVE LEARNING METHOD IN INSHA' LEARNING AT IAI AL-MUSLIM ACEH - Yusliza, Yusliza; Hizbullah, Auliya; Nur Annisa, Akrima; Aminah, Aminah (Program Studi Pendidikan Bahasa Arab, 2025)
The Insya' (Arabic Composition) learning, as part of Arabic writing skills, often faces challenges such as low active participation from students and the limited use of teaching methods that support creativity. The cooperative learning method of the Student Teams Achievement Divisions (STAD) type offers an innovative solution to address these issues. This study aims to analyze the implementation of the STAD method in Insya' learning among students of the Arabic Language Education Program at the Islamic Institute of Al-Muslim Aceh. The research employs a qualitative descriptive approach, with data obtained through documentation of the Semester Learning Plan (RPS). The analysis technique used is the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing. The study's findings illustrate that implementing the STAD method involves components such as class presentations, group work, quizzes, individual score improvement, and group rewards. This implementation highlights how students can collaborate, share ideas, and support each other in the Insya' learning process. The study concludes that the STAD type of Cooperative Learning method is an approach that can be effectively applied in the Insya' learning process